The Impact of ECSR and Innovation on Purchase Intentions: The Moderating Role of Green Corporate Image - Rahayu, Aditya Fajar; Wibowo, Mas Wahyu (Universitas Mercu Buana, 2025)
This research examines how Green Innovation, ECSR, and Service Innovation affect Purchase Intention, utilizing Green Corporate Image as a moderator. Quantitative data from 233 procurement experts was obtained. The research analyzed data using SEM-PLS. Service Innovation strongly affects Purchase Intention, but Green Innovation and ECSR do not. However, Green Corporate Image enhances the link between ECSR and Purchase Intention while weakening Service Innovation. These results show that company image is critical to customer choices in sustainability-driven businesses.Objectives: Sustainability has become a key concern for businesses, particularly in industries that rely on environmental resources. This study aims to explore how Green Innovation, Environmental Corporate Social Responsibility (ECSR), and Service Innovation influence Purchase Intention, with Green Corporate Image acting as a moderating factor. The goal is to provide insights into how companies in the integrated water supply sector can leverage sustainability-driven strategies to enhance consumer decision-making.Finding: This study uses quantitative Structural Equation Modeling-Partial Least Squares. 233 procurement experts completed a 7-point Likert scale survey. Using SmartPLS 4, the research investigated variable associations for reliability and validity.Conclusion: This study provides valuable insights into how businesses in the integrated water supply sector can integrate sustainability and innovation into their marketing strategies. While Service Innovation plays a crucial role, Green Innovation and ECSR require strong corporate branding to influence consumer behavior. Companies should focus on strengthening their environmental image while maintaining service excellence to maximize customer engagement. Future research should explore other moderating factors and examine industry-specific differences to refine sustainability-driven marketing strategies.